Augmented reality borobudur temple: Development of the aves booklet on the avadana relief story - Dini, Mia Saktian; Darmawan, Ericka; Sukmawati, Ika (STKIP Persada Khatulistiwa Sintang, 2024)
The issue identified in the aves sub-material for the class The media has not provided a thorough explanation of the structure and morphology of birds. The objective of this study is to create aves booklet media using augmented reality technology and evaluate its appropriateness through expert evaluations and user feedback. The study methodology employed is exploratory descriptive research, which is subsequently followed by development research utilizing the ADDIE model. Utilizing validation evaluation instruments for data analysis. The review of the augmented reality-based Aves booklet by media experts yielded a validity and feasibility score of 91.6%, while material specialists rated it at 80%. Meanwhile, Biology teachers rated the user reaction to augmented reality-based aves booklets as 92.5, indicating a very excellent evaluation. Similarly, students' user responses received a rating of 83.25%, indicating a good assessment.